2020
DOI: 10.1038/s41598-020-68002-5
|View full text |Cite
|
Sign up to set email alerts
|

High-performance thermochromic VO2-based coatings with a low transition temperature deposited on glass by a scalable technique

Abstract: We report on high-performance thermochromic ZrO2/V0.982W0.018O2/ZrO2 coatings with a low transition temperature prepared on glass by a low-temperature scalable deposition technique. The V0.982W0.018O2 layers were deposited by a controlled high-power impulse magnetron sputtering of V target, combined with a simultaneous pulsed DC magnetron sputtering of W target to reduce the transition temperature to 20–21 °C, at a low substrate surface temperature of 330 °C in an argon–oxygen gas mixture. ZrO2 antireflection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 40 publications
0
46
0
Order By: Relevance
“…The coating performance strongly depends on the thickness of the bottom and the top AR layer (hb and ht, respectively). It has been detailed [26] and experimentally justified [25,26] that while the There are data below T tr (full symbols) and above T tr (empty symbols), obtained on the ultrathin FG substrate (triangles up) and SLG substrate (triangles down) using the transmittance (T) and the reflectance (R) presented in Figure 6.…”
Section: Coating Designmentioning
confidence: 97%
See 2 more Smart Citations
“…The coating performance strongly depends on the thickness of the bottom and the top AR layer (hb and ht, respectively). It has been detailed [26] and experimentally justified [25,26] that while the There are data below T tr (full symbols) and above T tr (empty symbols), obtained on the ultrathin FG substrate (triangles up) and SLG substrate (triangles down) using the transmittance (T) and the reflectance (R) presented in Figure 6.…”
Section: Coating Designmentioning
confidence: 97%
“…The coating performance strongly depends on the thickness of the bottom and the top AR layer (h b and h t , respectively). It has been detailed [26] and experimentally justified [25,26] that while the usual thin quarter-wavelength AR layers lead to a maximum T lum at a very low ∆T sol , thicker three quarter-wavelength AR layers lead to maxima of both T lum (due to the second-order interference in the visible) and ∆T sol (due to the first-order interference in the near infrared where most of the energy saving takes place). This leads to an optimum optical path length of ZrO 2 corresponding to, e.g., h b = h t = 180 nm at n 550 = 2.15 (value considered in [26]) and similarly for other n 550 values.…”
Section: Coating Designmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, to increase the luminous transmittance of VO 2 films, antireflection coatings or structures are adopted. For instance, Kolenaty et al reported a three-layer structure, with ZrO 2 antireflective layers acting as a protection layer and structure template [49]. Several works have used SiO 2 , TiO 2 , and ZrO 2 antireflective layers [37].…”
Section: Thermochromic Materialsmentioning
confidence: 99%
“…Doped VO 2 is commonly prepared by hydrothermal synthesis [6], chemical vapour deposition [14], magnetron sputtering [15], sol-gel synthesis [16], etc. Although these methods usually require long-lasting thermal treatment at high temperatures in an inert atmosphere, VO 2 films can be successfully prepared by fairly low temperature magnetron sputtering depositions [17][18][19][20]. Nevertheless, VO 2 can be prepared by means of facile wet-chemistry synthesis through intermediate vanadyl glycolate, VO(OCH 2 CH 2 O), thus enabling short annealing times and avoiding inert atmosphere requirements [21].…”
Section: Introductionmentioning
confidence: 99%